Factors Affecting Central Node Metastasis and Metastatic Lymph Node Ratio in Papillary Thyroid Cancer. (9th February 2021) - Seok, Jungirl; Ryu, Chang Hwan; Park, Seog Yun; Lee, Chang Yoon; Lee, Young Ki; Hwangbo, Yul; Lee, Eun Kyung; Lee, You Jin; Kim, Tae Sung; Kim, Seok‐ki; Jung, Yuh‐Seog; Ryu, Junsun
Abstract : Objective: Despite the growing evidence that metastatic lymph node ratio (MLNR) is a valuable predictor for the prognosis of papillary thyroid carcinoma, it has not yet been fully determined which factors give the ratio predictive value independent of the number of metastatic lymph nodes (MLNs). Study Design: Retrospective cohort study. Setting: A comprehensive cancer center. Methods: Recurrence and clinicopathologic factors were analyzed in 2409 patients with papillary thyroid carcinoma who underwent total thyroidectomy and central node dissection. Results: Cutoff values of MLNs ≥2 and MLNR ≥28.2% increased the recurrence risk (hazard ratio [95% CI], 9.97 [4.73‐21.0] and 11.4 [5.53‐23.3], respectively). Younger age, male sex, multifocality, tumor size, lymphatic and vascular invasion, and gross extrathyroidal extension positively correlated with MLN and MLNR (all P <. 05). Meanwhile, lymphocytic thyroiditis negatively correlated with MLNR in female patients ( P <. 001), by increasing total lymph node yields as compared with papillary thyroid carcinoma without lymphocytic thyroiditis. In multivariate analysis, younger age, tumor size, and lymphatic invasion remained significant in male and female patients for MLN and MLNR; lymphocytic thyroiditis was also significantly correlated with MLNR in female patients. Conclusion: Our study demonstrates that MLN and MLNR are independently observed prognostic markers for tumor recurrence. However, lymphocytic thyroiditis in female patients seems to have lower MLNR by increasing total lymph node yields. In light of their association, a different cutoff for MLNR needs to be applied according to the presence or absence of underlying lymphocytic thyroiditis in the use of MLNR for predicting the recurrence. Level of Evidence: 4.